Effect of administrative information on visit rate of frequent attenders in primary health care: ten-year follow-up study - Anne K. Santalahti; Tero J. Vahlberg; Sinikka H. Luutonen; Päivi T. Rautava (BMC, 2022)
Background: frequent attenders (FAs) use a disproportionately large share of the resources of general practitioners (GPs) working in primary healthcare centres. The aim of this study was to estimate the proportion of FAs among all patients in the primary health care centres of a medium-sized city in Finland, and to examine whether providing GPs with administrative information about their frequent attenders (names and numbers of visits per year) can reduce the number of FAs and the frequency of their visits.Methods: Statistic data on all GP visits (n = 1.8 million) to 11 public healthcare centres in one city were collected from the electronic patient records covering the period from 2001 to 2010. A FA-patient was defined as a person who made10 or more visits to GPs during one year. The baseline situation in 2001 was compared with the situation in 2006 after administrative information had been provided three times to all GPs working in the healthcare centres. Poisson's regression analysis was used, and FA numbers and consultation rates in the years 2002-2005 were compared with the year 2006; figures for 2006 were also compared with those for the follow-up period 2007-2010.Results: During the years 2001-2006, the proportion of visits of FA-patients fell overall from 9.1 to 8.5%, a decline of 0. 6% (p < 0.0001). This reduction was equivalent to an annual work load of two GPs in the study center. The proportion of visits of FA patients increased again in the follow-up period (2007-2010), when administrative information was no longer provided.Conclusion: When GPs are provided with information on the number and names of their FA-patients, the annual rate of FA visits to GPs drops significantly. The method is simple and repeatable. However, without a control group of GPs who have not received such information, it is impossible to assess if the intervention was the only circumstance affecting the reduction in FA consultation rates.